Developing a Mixed Reality-based 3D Virtual Laboratory for Multimedia Practicum: A Metaverse Approach - Padmasari, Ayung Candra; Hizbillah, Muhammad Ridwan Alfarizi; As'ari, Muhammad Agung (CV. Media Inti Teknologi, 2025)
Background of study: Although learning media have experienced growth and variation, the trend of implementing online learning that is in accordance with the needs of the times has not fully answered the needs of students in learning independently. Specific needs, especially in skill-based fields such as multimedia, electronics, automotive, and health. The transition to online practicums has been problematic due to limited access to digital versions of tools and materials, as well as restrictions on the use of physical laboratories during the pandemic.Aims and scope of paper: This study focuses on the development of a contextually relevant educational technology solution: a 3D virtual laboratory that uses mixed reality to support online multimedia practicums. Mixed reality allows users to interact with realistic audio-visual elements such as sounds, colors, environmental activities, and specific objects, allowing for immersive navigation in a virtual setting. Incorporating Metaverse features further enhances interactivity in the virtual classroom.Methods: This study adopted the Multimedia Development Life Cycle (MDLC) method.Result: The results show that the 3D virtual laboratory meets all five usability criteria, namely, Ease of Learning (86.7%), System Performance (80.5%), Efficiency (87.1%), Ease of Finding (84.3%), and Fun (83.1%) which confirms its effectiveness as a usable and engaging learning tool.Conclusion: With the design of a 3D virtual laboratory based on mixed reality as an innovation in online multimedia practicum media, it is expected to be a new form of innovation in packaging practicum media that is more interactive and useful for distance learning activities.